Environmental impacts related to the commissioning and usage phase of an intelligent energy management system. (15th January 2015) - Gangolells, Marta; Casals, Miquel; Forcada, Núria; Macarulla, Marcel; Giretti, Alberto
Highlights: An intelligent energy management system for underground metro stations is examined. The assembly phase involves an environmental impact of 897.02 Eco-indicator'99 points. The monitoring subsystem dominates the environmental impact. Considering a 5–10-year lifespan, the impact ranges between 1963 and 3029 Eco-points. The impact on resources is the largest, followed by human health and ecosystem quality. Abstract: This paper presents for the first time the results of a life cycle assessment study for an intelligent energy management system. We considered material acquisition, manufacturing, transportation, assembly, operation and maintenance stages. The results show that the assembly phase had an environmental impact of 897 Eco-indicator 99 points that was mainly due to the monitoring subsystem (87.80%). When the analysis was extended to cover the use phase, the environmental impact ranged from 1963 (useful life of 5 years) to 3029 Eco-indicator 99 points (useful life of 10 years). The environmental impact of the use stage was found to represent 54–70% of the total, whereas the assembly stage represented 46–30%. The maintenance phase contributed to a very small extent to the total environmental impact (less than 0.5%). In any case, the impact on resources was the largest (about 51%), whereas the human health damage category amounted to approximately 35% and the ecosystem quality damage category represented about 14% of the total impact.